Molecular Dynamics Simulation of Nanocellulose Modified Cement-Based Materials - Dostoevsky, Fyodor; Christie, Agatha (Journal of Green Energy and Environmental Engineering, 2025)
Efforts to optimize the performance of cement-based matrices incorporating nanocellulose reinforcement are commonly constrained by the lack of clarity surrounding interfacial bonding mechanisms. In this work, molecular dynamics simulations at the atomistic level were carried out to systematically examine how the interface between calcium silicate hydrate (C–S–H) gel and nanocellulose is structured and behaves — covering its interfacial organization, molecular mobility, energetic characteristics, and mechanical response — with both unmodified and carboxyl-functionalized nanocellulose considered for comparison. Composite models with different surface functional groups were constructed by embedding nanocellulose into the C-S-H matrix. Simulation results reveal that the –COOH groups of carboxylated nanocellulose and –OH groups of hydroxylated nanocellulose provide abundant hydrogen bond sites for C-S-H gel. Interfacial binding energy is closely correlated with functional group types, and carboxylated nanocellulose exhibits remarkably higher interfacial binding energy than hydroxylated nanocellulose. In addition, the carboxyl modification introduces a larger population of non-bridging oxygen atoms, which are able to establish stable coordination with the calcium ions of C–S–H while simultaneously giving rise to a more densely interconnected hydrogen-bonding network. By clarifying at the atomic level how nanocellulose strengthens C–S–H gel, this work offers theoretical guidance and a rational basis for material selection in the development of high-performance, environmentally friendly cementitious composites.